Realization of 3D reflectors by using metal-air and semiconductor-air based photonic structures at three communication windows - Mohanty, S.P.; Sahoo, S.K.; Mishra, C.S.; Panda, A.; Palai, G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
This study is based on an analysis of a 3D photonic crystal structure (PCS) for the realization of a photonic reflector pertaining to suitable optical communication wavelengths of 850, 1310, and 1550 nm. The said photonic reflector application is envisaged separately by two 3D PCSs, which comprise semiconductor (germanium) and metal (iron) based circular rods respectively, arranged on a square lattice having air as the background material. The plane wave expansion (PWE) technique is employed to investigate the photonic band gap (PBG) vis-à-vis all the aforementioned wavelengths. PBG is meticulously controlled by suitably selected various structural parameters, such as lattice spacing, diameter of the circular rods, and nature of their material. Simulation outcomes explored that semiconductor-based PCS reflects wavelengths of 850, 1310, and 1550 nm, when selecting the diameter of the circular rods as 282, 608, and 771 nm, respectively, whereas metal-based PCS reflects the aforementioned wavelengths for diameters of the circular rods close to 335, 1070, and 871 nm, respectively. Further, we assayed the variation in reflected wavelength with respect to different diameters of circular rods for both proposed structures. Thus, the proposed optical reflectors can find a wide range of applications vis-à-vis three communication windows. Це дослідження базується на аналізі тривимірної структури фотонного кристала для створення фотонного відбивача, що відноситься до відповідних довжин хвиль оптичного зв’язку 850, 1310 і 1550 нм. Зазначене застосування фотонного відбивача передбачається окремо двома 3D-структурами фотонного кристала, які містять напівпровідникові (германій) або металеві (залізо) кругові стрижні відповідно, розташовані на квадратній решітці, що містить повітря як фоновий матеріал. Метод розширених плоских хвиль застосовується для дослідження фотонної забороненої зони по відношенню до всіх вищезазначених довжин хвиль. Фотонна заборонена зона ретельно контролюється за допомогою відповідно вибраних різних параметрів структури, таких як відстань між гратами, діаметр кругових стрижнів та властивості матеріалу. Результати моделювання показали, що структура фотонного кристала на основі напівпровідника відбиває хвилі довжиною 850, 1310 і 1550 нм, у випадку діаметра кругових стрижнів 282, 608 і 771 нм відповідно, тоді як структура фотонного кристала на основі металу відбиває хвилі згаданої довжини для діаметра кругових стрижнів 335, 1070 та 871 нм відповідно. Далі ми проаналізували зміну відбитої довжини хвилі щодо різного діаметра кругових стрижнів для обох запропонованих структур. Таким чином, запропоновані оптичні відбивачі можуть знайти широкий спектр застосувань щодо трьох комунікаційних вікон.